Transition scaling of the immature strike-slip fault damage zone in the central Sichuan Basin (SW China) - Liu, Xiaoxu; Wu, Guanghui; Chen, Hailong; Long, Hui; Tang, Song; Su, Chen; Tian, Weizhen (Frontiers in Earth Science, 2025)
Immature faults typically exhibit a linear scaling between damage zone width and displacement up to a certain displacement threshold. However, the nature and precise value of this threshold remain debated. In this study, we investigate five immature strike-slip fault damage zones and their scaling relationships in the central Sichuan Basin using seismic data. The widths of the seismic damage zones are consistent with borehole data and show a correlation with the vertical displacement (throw) in Ediacaran carbonate rocks. The damage zone widths are found to be approximately 3–7 times larger than the vertical throw, exhibiting an overall linear scaling relationship. As the vertical throw increases, three of the faults maintain this linear scaling with increased data scatter. In contrast, two faults display a power-law transition in scaling when the vertical throw ranges from 50 m to 80 m and then return to a linear trend once the throw exceeds 130 m. Notably, the transition in scaling emerges when the damage zone width exceeds 600 m. These findings suggest that the scaling transition between fault damage zone width and displacement cannot be constrained by a fixed displacement threshold. Furthermore, the damage zones of immature strike-slip faults may exhibit variable off-fault damage evolution, transitioning from linear to power-law scaling as displacement increases.